Multi-scale biodiverity patterns in phytoplankton from coastal lagoons: The eastern mediterranean - Roselli, L.; Stanca, E.; Ludovisi, A.; Durante, G.; Souza, J.S.D.; Dural, M.; Basset, A. (My University, 2013)
1 - The phytoplankton from Eastern Mediterranean coastal lagoons is analysed using a multi-scale approach, with the aim of testing if phytoplankton variations follow a hierarchical scheme based on eco-geographical location. The scale similarity is examined by using a taxonomic metric based on the Kullback-Leibler divergence and a related similarity index. 2 - A hierarchical sampling design was used to investigate variations in taxonomic composition and richness of phytoplankton assemblages. Data analyzed collected during summer season in 3 coastal lagoons in the Mediterranean Eco-region: two are located in Turkey (Akgöl and Paradeniz) and one is located in Greece (Korission). According to the Mediterranean typology, all lagoons are large, non-tidal and have mean salinity regimes of oligohaline (Akgöl), polyhaline (Paradeniz) and euhaline (Korission) designations. 3 - The taxonomic composition of phytoplankton assemblages varied markedly among lagoons, with the most representative phytoplankton in terms of taxa richness belonged to Chlorophyceae (33.33%) in Akgöl, to Dinophyceae (50.00%) in Paradeniz and to Dinophyceae (30.77%) in Korission. 4 - Within-habitat similarity was very high in all habitats and lagoons. At an ecosystem scale, phytoplankton was highly homogeneous in Akgöl and Paradeniz, suggesting that the distinctive physiognomic traits of the habitats exert a limited effect. In contrast, the phytoplankton is significantly heterogeneous in Korission, mostly because of the effect of the heterogeneous habitats, in fact the three sampled habitats showed well-differentiated characteristics. 5 - At an eco-regional scale, the pattern of similarity among lagoons suggests that local conditions (particularly salinity) and geographical location play roles of a comparable importance in determining the dissimilarity among phytoplankton guilds. 6 - The similarity index between adjacent lagoons having different salinity (Akgöl and Paradeniz) was comparable to the one between lagoons with similar salinity but different geographical location. This suggests that local conditions and geographical factors act in a complex way. © 2013 University of Salento- SIBA.
Keywords: Biodiversity; Coastal lagoons; Mediterranean eco-region; Multi-scale approach; Phytoplankton; Taxonomy